In vitro propagation of banana (Bangladesh Journal of Agricultural Research, 2010)
An in vitro technique for plant regeneration using meristem-derived plantlets of banana cv. BARI-l (Musa sp.) has been developed. Highest number of shoot regeneration was noticed on basal media supplemented with 7.5 mgL-1 BAP + 0.5 mgL-1 NAA at 30 days after inoculation (DAI). The mean number of shoots significantly reduced when the concentrations of BAP and NAA in the medium was high. Regenerated shoots were rooted on half strength MS medium containing 0.5 mgL-1 IAA + 0.5 mgL-1 IBA at 30 DAI. In vitro raised plantlets were transferred to poly bags containing ground soil and cowdung mixture (1:1) for acclimatization and hardening in room temperature (28-30°C) and the established plantlets are ready for planting in the field. Key Words: In vitro propagation; banana; Musa sp.DOI: 10.3329/bjar.v34i2.5799Bangladesh J. Agril. Res. 34(2): 269-278, June 2009